Власні імена та варіанти імен жителів Підляшшя - Нестерчук, Оксана Григорівна; Nesterchuk, Oksana H. (Uniwersytet Przyrodniczego w Lublinie, 2010)
У статті проаналізовані власні імена та їх варіанти жителів Підляшшя та встановлено спосіб їх творення. Виявлено, що деякі варіанти власних імен запозичені з польської мови, це відображає тісні контакти між українцями і поляками на Підляшші. The article deals with proper names and variations of proper names of Pidliashshia region inhabitants, attesting that the method of their composing is similar to those which are used in other regions of Ukraine. Additionally some variants of proper names are borrowed from polish language, what reflects tight contacts among Ukrainians and Poles in this region.
Proper names, and variations of Pidliashshia region habitants
Keywords: власні імена; варіанти; суфікси; словотвір; variations; proper names; article; composing